Potential of indigenous entomopathogenic fungi diversity in the maize rhizosphere - Septia Erfan Dani; Sukorini Henik (BIO Web of Conferences)
Modern agriculture faces significant overreliance on chemical pesticides, leading to environmental pollution and pest resistance. As a promising alternative, entomopathogenic fungi (EPF) offer a biological approach to pest control. This study investigates the hypovirulence and virulence effects of EPF on corn and cucumber plants by measuring their Disease Severity Index (DSI). The treatment involves isolating and applying fungi to seeds to observe their pathogenic impact. The DSI, which measures disease intensity, is used to determine whether the fungi are virulent (DSI ≥ 2) or hypovirulent (DSI < 2). The virulence treatment involves exposing seedlings to fungal isolates and monitoring symptoms, such as brown hypocotyls, withered leaves, or seed death. Isolates like J5S1U2, J3S1U2, J2S2U1, and J2SU4 were found to be virulent towards cucumber, causing abnormal germination and severe stress. In contrast, hypovirulent isolates, such as J4S2U2, J3S2U1, and T5U1O, caused mild symptoms, including light brown patches under 0.5 cm on hypocotyls without significant wilting, making them safer for agricultural use. The treatment approach emphasizes selecting fungal isolates based on crop-specific virulence, aiming to optimize pest control strategies. Hypovirulent isolates, in particular, are identified as suitable candidates for integrated pest management, as they minimize plant stress while offering effective biological control.